Highly-fair bakery algorithm using symmetric tokens - Aravind, Alex A. (Information processing letters, 2010)
This note proposes a new version of the bakery algorithm that: (i) assures fair tie-breaking when two or more processes choose same token number; and (ii) bounds the token numbers within the range [ − n , n ] . The algorithm is simple and uses one additional shared bit. ► New mutual exclusion algorithm. ► Fair mutual exclusion algorithm. ► Improved bakery algorithm. ► Bakery algorithms with bounded tokens.